"Taste modification" strategy for prevention and control of hypertension in India: need for robust clinical trials - Sudip Bhattacharya; Saurabh Varshney; Md Mahbub Hossain; Sheikh Mohd Saleem; Pratima Gupta; Amarjeet Singh (Elsevier, 2023)
Summary: Hypertension is an important modifiable risk factor for cardiovascular disease (CVD). Among normotensives, excessive dietary salt elevates the blood pressure and thereby increases the risk of CVD events. Despite such solid evidence, there is no effective approach to address excessive salt intake in India. Instead of just encouraging patients to lower their salt intake, we must provide an alternative technique by fostering an environment that facilitates this behaviour change. In this Viewpoint, we propose 'Taste Modification' strategy, i.e., a salt-reduction technique in which individuals are informed that adding spices/herbs to meals will reduce their salt intake. We hypothesise that a gradual reduction in salt intake can aid in the treatment of hypertension over time. The goal is to progressively substitute salt with spices for effective salt reduction. However, the 'Taste Modification' strategy must be first validated using multicentric clinical trials.